2019
DOI: 10.1002/ar.24244
|View full text |Cite
|
Sign up to set email alerts
|

Ramification Pattern of the Arteries Supplying the Rabbit Female Genital Organs

Abstract: Uterine adenocarcinoma occurs in more than 60% of female rabbits aged 4 years and over. To cure or prevent this uterine disorder, ovariohysterectomy should be performed. Although knowledge of the arterial supply to the ovary, uterus, and vagina is required, few studies have described the arterial anatomy. Therefore, we dissected ovarian, uterine, and vaginal arteries in 15 New Zealand White and 15 Japanese White rabbits to clarify the anatomy. The ovarian artery arose from the abdominal aorta, and in 50% of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The right OA emanated before the left one from the abdominal aorta, which was verified in rabbits [43], and chinchilla [44]. Our finding asserted that the OA releases uterine, tubal, and ovarian branches, which was confirmed by Kigata and Shibata [45]; however, this is inconsistent with the finding of Milanović et al [43]. Therefore, the OA is responsible for ovarian, oviduct, ovarian bursa, and uterine horn nutrition in rabbits [43], and bitch [46].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The right OA emanated before the left one from the abdominal aorta, which was verified in rabbits [43], and chinchilla [44]. Our finding asserted that the OA releases uterine, tubal, and ovarian branches, which was confirmed by Kigata and Shibata [45]; however, this is inconsistent with the finding of Milanović et al [43]. Therefore, the OA is responsible for ovarian, oviduct, ovarian bursa, and uterine horn nutrition in rabbits [43], and bitch [46].…”
Section: Discussionsupporting
confidence: 72%
“…Therefore, the OA is responsible for ovarian, oviduct, ovarian bursa, and uterine horn nutrition in rabbits [43], and bitch [46]. The UA originated from the common iliac artery, which was inconsistent with the findings of Kigata and Shibata [45], who asserted that it emanated from the umbilical or common iliac artery. The UA is ramified to provide vaginal, cranial vesicular artery, and uterine branches, which is consistent with the findings of Kigata and Shibata [45].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we rst attempted to visualize and identify the uterine artery under CT. According to published data [19,20] , the uterine artery of female rabbits originates from the umbilical artery, which stems from the external iliac artery, a branch of the common iliac artery, which in turn is derived from the abdominal aorta. In this research, we observed the same anatomical distribution of arteries (Fig.…”
Section: Identify Uterine Artery Under Ct Scanningmentioning
confidence: 99%
“…In this study, we rst attempted to visualize and identify the uterine artery under CT. According to published data [19,20] , the uterine artery of female rabbits originates from the umbilical artery, which stems from the external iliac artery, a branch of the common iliac artery, which in turn is derived from the abdominal aorta. In this research, we observed the same anatomical distribution of arteries (Figure 1A).…”
Section: Identify Uterine Artery Under Ct Scanningmentioning
confidence: 99%